Does the measurement of four fetal arteries provide more information than the measurement of just two arteries in prenatal Doppler sonography? - Meyberg-Solomayer, Gabriele Christine; Solomayer, Erich-Franz; Grischke, Eva-Maria; Bastert, Gunther (Ultrasound in obstetrics & gynecology, 2002)
The objective of this study was to evaluate whether the measurement of two or more fetal arteries provides more information and leads to a selection of fetuses at higher risk.